The Importance of Marine Observatories and of RAIA in Particular - Bastos, Luísa; Bio, Ana; Iglesias, Isabel (Frontiers in Marine Science, 2016)
Coastal and Oceanic Observatories are important tools to provide information on ocean state, phenomena and processes. They meet the need for a better understanding of coastal and ocean dynamics, revealing regional characteristics and vulnerabilities. These observatories are extremely useful to guide human actions in response to natural events and potential climate change impacts, anticipating the occurrence of extreme weather and oceanic events and helping to minimize consequent personal and material damages and costs. International organizations and local governments have shown an increasing interest in operational oceanography and coastal, marine and oceanic observations, which resulted in substantial investments in these areas. A variety of physical, chemical and biological data have been collected to better understand the specific characteristics of each ocean area and its importance in the global context. Also the general public’s interest in marine issues and observatories has been raised, mainly in relation to vulnerability, sustainability and climate change issues. Data and products obtained by an observatory are hence useful to a broad range of stakeholders, from national and local authorities to the population in general. An introduction to Ocean Observatories, including their national and regional importance, and a brief analysis of the societal interest in these observatories and related issues are presented. The potential of a Coastal and Ocean Observatory is then demonstrated using the RAIA observatory as example. This modern and comprehensive observatory is dedicated to improve operational oceanography, technology and marine science for the North Western Iberian coast, and to provide services to a large range of stakeholders.